Caracterización De Germinado De Quinua (Chenopodium quinoa) - Cayambe Lema, Franklin Bolivar (2024)
In this research project, two types of quinoa samples were used: germinated and non-germinated. For the germinated quinoa, the sprouting method was applied, which facilitated the development of natural sprouts for optimal seedling growth King (2020). The physicochemical properties of both samples, including ash, fiber, fat, protein, calcium, iron, and manganese, were analyzed. Differences were observed between the samples, with germinated quinoa showing an increase in fiber content (5,36%) but a decrease in fat (2,27%), ash (1, 86%), and protein (8, 51%). Additionally, the germination process decreased the levels of micronutrients such as calcium (56, 01%), iron (3,29%), and manganese (1,80%). In contrast, non-germinated quinoa exhibited an ash content of (2,74%), fat content of (3,78%), fiber content of (3,24%), protein content of (9,24%), calcium content of (56,50%), iron content of(3,30%), and manganese content of (1,91%). The results indicated that germinated quinoa had higher values of fiber (5.36%), compared to nongerminated quinoa. Therefore, based on this study, germinated